Low cyclin F expression in hepatocellular carcinoma associates with poor differentiation and unfavorable prognosis. Issue 4 (17th February 2013) - Fu, Jia; Qiu, Huijuan; Cai, Muyan; Pan, Yinghua; Cao, Yun; Liu, Lili; Yun, Jingping; Zhang, Chris Zhiyi
<x xml:space="preserve">Abstract</x> Cyclin F, capable of forming Skp1‐Cul1‐F‐box protein ubiquitin ligase complex, is implicated in controlling centrosome duplication and preventing genome instability. Cyclin F oscillates during cell cycle with a similar pattern to cyclin A. However, its expression and significance in cancer remain obscure. In this study, we showed that cyclin F was noticeably decreased in 16 pairs of tissue samples of hepatocellular carcinoma (HCC) compared to paracarcinoma tissues, at both mRNA and protein levels. Immunohistochemical staining data revealed that in 71.8% (176/245) of HCC cases, cyclin F expression in tumor tissue was much lower than that in nontumorous tissue. Low cyclin F expression, defined by receiver operating characteristic curve analysis, was present in 69.0% of HCC patients. Low expression of cyclin F was significantly correlated with tumor size, clinical stage, serum alpha‐fetoprotein level and tumor multiplicity. Further study showed that cyclin F expression was reversely associated with tumor differentiation in HCC. Kaplan–Meier analysis indicated that low cyclin F expression was related to poor overall survival and recurrence‐free survival. The prognostic impact of cyclin F was further confirmed by stratified survival analysis. Importantly, multivariate analysis revealed that low cyclin F expression was an independent poor prognostic marker for overall survival. We conclude that cyclin F is downregulated in HCC and is a promising prognostic marker for patients suffering from this deadly disease.